Peelable Nanocomposite Coatings: "Eco-Friendly" Tools for the Safe Removal of Radiopharmaceutical Spills or Accidental Contamination of Surfaces in General-Purpose Radioisotope Laboratories - Traian Rotariu; Daniela Pulpea; Gabriela Toader; Edina Rusen; Aurel Diacon; Valentina Neculae; John Liggat (MDPI AG, 2022)
Radioactive materials are potentially harmful due to the radiation emitted by radionuclides and the risk of radioactive contamination. Despite strict compliance with safety protocols, contamination with radioactive materials is still possible. This paper describes innovative and inexpensive formulations that can be employed as 'eco-friendly' tools for the safe decontamination of radiopharmaceuticals spills or other accidental radioactive contamination of the surfaces arising from general-purpose radioisotope handling facilities (radiopharmaceutical laboratories, hospitals, research laboratories, etc.). These new peelable nanocomposite coatings are obtained from water-based, non-toxic, polymeric blends containing readily biodegradable components, which do not damage the substrate on which they are applied while also displaying efficient binding and removal of the contaminants from the targeted surfaces. The properties of the film-forming decontamination solutions were assessed using rheological measurements and evaporation rate tests, while the resulting strippable coatings were subjected to Fourier-transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), and tensile tests. Radionuclide decontamination tests were performed on various types of surfaces encountered in radioisotope workspaces (concrete, painted metal, ceramic tiles, linoleum, epoxy resin cover). Thus, it was shown that they possess remarkable properties (thermal and mechanical resistance which permits facile removal through peeling) and that their capacity to entrap and remove beta and alpha particle emitters depends on the constituents of the decontaminating formulation, but more importantly, on the type of surface tested. Except for the cement surface (which was particularly porous), at which the decontamination level ranged between approximately 44% and 89%, for all the other investigated surfaces, a decontamination efficiency ranging from 80.6% to 96.5% was achieved.